Fat Embolism Syndrome Secondary to Bone Marrow Necrosis in Patients with Hemoglobinopathies. Issue 9 (September 2016) - Gangaraju, Radhika; Reddy, Vishnu V.B.; Marques, Marisa B.
Abstract : Abstract: Bone marrow necrosis with subsequent embolization of the fat and necrotic tissues into the systemic circulation causing fat embolism syndrome and multiorgan failure is a rare complication of patients with hemoglobinopathies. The exact etiology of this condition is not known. Because it occurs more often in patients with compound heterozygous conditions than in sickle cell disease, some patients are unaware of their predisposition. The initial symptoms are nonspecific, such as back and/or abdominal pain, fever, and fatigue, which may rapidly progress to respiratory failure and severe neurologic compromise. Common laboratory tests reveal anemia without reticulocytosis, thrombocytopenia, leukoerythroblastic picture with immature white cells and nucleated red blood cells, increased lactate dehydrogenase, high ferritin, and, sometimes increased creatinine. The diagnosis can be delayed because of an apparent lack of awareness about bone marrow necrosis with fat embolism syndrome, its rarity, and its similarities with other conditions such as thrombotic thrombocytopenic purpura. Although a bone marrow biopsy is diagnostic, waiting for it delays definitive treatment, which appears to be essential for the recovery of end-organ damage, such as neurologic and pulmonary damage. In our experience, either multiple units of red blood cell transfusion or, preferably, red cell exchange initiated promptly, is lifesaving. Abstract : Bone marrow necrosis with fat embolism syndrome is a rare complication of sickle cell disorders. With this review, we hope to increase awareness of this rare entity by describing its common presenting clinical and laboratory features, clinical significance, and management options.